2014
DOI: 10.1016/j.ajo.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Filamentous Fungal Isolates From a Corneal Ulcer Clinical Trial

Abstract: Purpose To describe the minimum inhibitory concentration (MIC) of fungal isolates to natamycin and voriconazole, and to compare these MICs to previous ocular susceptibility studies. Design Experimental laboratory study using isolates from a randomized clinical trial. Methods The Mycotic Ulcer Treatment Trial I was a randomized, double-masked, multicenter trial comparing topical natamycin and voriconazole for fungal keratitis treatment. Susceptibility testing to natamycin and voriconazole were performed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
3
39
0
1
Order By: Relevance
“…were resistant to VRC and hence higher concentration of drug is required for the effective treatment. However, there are studies that have suggested that VRC may have a broader antifungal spectrum [19,20]. Similar to our findings, Lalitha et al [17] and Iqbal et al [31] stated that Fusarium spp.…”
Section: Resultssupporting
confidence: 93%
“…were resistant to VRC and hence higher concentration of drug is required for the effective treatment. However, there are studies that have suggested that VRC may have a broader antifungal spectrum [19,20]. Similar to our findings, Lalitha et al [17] and Iqbal et al [31] stated that Fusarium spp.…”
Section: Resultssupporting
confidence: 93%
“…However, a prominent fungal exception to this rarity is A. flavus which not only causes toxic seed diseases but also is a common agent of keratitis as well as a frequent pathogen of immunosuppressed patients [26,38]. This fungus is common in agricultural soils and hard to eliminate from that environment due to formation of resistant overwintering structures called sclerotia.…”
Section: Discussionmentioning
confidence: 99%
“…Although several fungi were sensitive to natamycin, the authors concluded that the treatment outcome was poor in late stages 20. In another in vitro study by Lalitha et al 21 MIC of both natamycin and voriconazole in mycotic ulcer treatment for filamentous fungi have been described. The authors concluded that Fusarium isolates were least susceptible to voriconazole, and Aspergillus flavus isolates were least susceptible to natamycin 21.…”
Section: Discussionmentioning
confidence: 98%